Efektivitas Peran Kader Dalam Penurunan Kejadian Stunting Pada Balita - Denny Novita Mayangsari (CV. ULIL ALBAB CORP, 2024)
Stunting in children under five remains a significant public health challenge in Indonesia. This study aims to analyze the effectiveness of community health workers' roles in reducing stunting incidence among children under five through a systematic review. A systematic review method was used to analyze 10 studies conducted in Indonesia between 2022-2023. The results show that community health workers play a significant role in reducing stunting, primarily through community education, early detection and initial management. Factors influencing the effectiveness of community health workers include knowledge and skill levels, training quality, policy support, and the use of innovative technologies. Variations in effectiveness across regions highlight the importance of adapting strategies to local contexts. In conclusion, the role of community health workers is effective in reducing stunting incidence, but requires a comprehensive approach and sustainable system support to optimize its impact.